KOMIK BERBASIS KEARIFAN LOKAL TERINTEGRASI AL ISLAM DAN KEMUHAMMADIYAHAN MATERI PERPINDAHAN KALOR - Ika Nurul Afifatus Sa’idah; Nur Ngazizah; Arum Ratnaningsih (Jurnal Binagogik, 2024)
This research aims to develop and test Comic Media Based on Integrated Local Wisdom of Al Islam and Muhammadiyah as a means to convey learning material. This research uses the R&D method with the ADDIE stages. The stages are analyze, design, development, implementation, and evaluation. The data collection techniques used were observation, interviews and questionnaires. The data analysis technique uses a limited test with 5 subjects and a broad test with 20 subjects. The results of this research: 1) A comic product based on local wisdom integrated with Al Islam and Kemuhammadiyahan, material on class V heat transfer at SD Muhammadiyah Purwodadi. 2) The feasibility results consist of: a) Validation of science material experts 90%, AIK material experts 94% (very valid), media experts 74% (valid), and practitioners 100% (very valid). b) The practicality of students' responses from limited trials got 100% and extensive trials got 93%. The results of the implementation of learning at meeting 1, observer I got a percentage of 97% and observer II got a percentage of 95% and at meeting II observers I and II got a percentage of 97% which was categorized as very practical. c) Effectiveness is obtained from N-Gain analysis and the AIK observation sheet. N-Gain analysis through a one group pretest posttest design got 0.7 with effective criteria. The AIK observation sheet from the religious aspect and the independent aspect received 3.5 and 3.4 with very effective criteria. From the results of validity, practicality and effectiveness, comics based on integrated local wisdom of Al Islam and Kemuhammadiyahan can be said to be suitable for use.